Partial Restoration of Spinal Cord Neural Continuity via Sural Nerve Transplantation Using a Technique of Spinal Cord Fusion - Ren, Xiaoping; Zhang, Weihua; Mo, Jian; Qin, Jie; Chen, Yi; Han, Jie; Feng, Xinjian; Han, Linxuan; Feng, Sitan; Liang, Haibo; Cen, Liangjue; Wu, Xiaofei; et al. (Frontiers in Neuroscience, 2022)
Background: Spinal cord injury (SCI) can cause paralysis and serious chronic morbidity, and there is no effective treatment. Based on our previous experimental results of spinal cord fusion (SCF) in mice, rats, beagles, and monkeys, we developed a surgical protocol of SCF for paraplegic human patients. We designed a novel surgical procedure of SCF, called sural nerve transplantation (SNT), for human patients with lower thoracic SCI and distal cord dysfunction. Methods: We conducted a clinical trial (ChiCTR2000030788) and performed SNT in 12 fully paraplegic patients due to SCI between T1 and T12. We assessed pre- and postoperative central nerve pain, motor function, sensory function, and autonomic nerve function. Conduction of action potentials across the sural nerve transplant was evaluated. Neural continuity was also examined by diffusion tensor imaging (DTI). Results: Among the 12 paraplegic patients enrolled in this clinical trial, seven patients demonstrated improved autonomic nerve functions. Seven patients had clinically significant relief of their symptoms of cord central pain. One patient, however, developed postoperative cord central pain (VAS: 4). Five patients had varying degrees of recovered sensory and/or motor functions below the single neurologic level one month after surgery. One patient showed recovery of electrophysiologic, motor-evoked potentials six months after the operation. At six months after surgery, DTI indicated fusion and nerve connections of white cord and sural nerves in seven patients. Conclusions: SNT was able to fuse the axonal stumps of white cord and sural nerve and at least partially improve the cord central pain in most patients. Although SNT did not restore the spinal cord continuity in white matter in some patients, SNT could restore spinal cord continuity in the cortico‑trunco‑reticulo‑propriospinal pathway, thereby restoring in part some motor and sensory functions. SNT may therefore be a safe, feasible, and effective method to treat paraplegic patients with SCI. Future clinical trials should be performed to optimize the type/technique of nerve transplantation, reduce surgical damage, and minimize postoperative scar formation and adhesion, to avoid postoperative cord central pain.